People Recognition: A Historical/Anthropological Perspective - A. Ardila (Behavioural Neurology)
Using current neurological and neuropsychological literature, and the analysis of different cultural and historical conditions, people recognition is analyzed. Different “subsystems” or “modules” could be involved in individuals' recognition: living versus non-living, own species versus other species, familiar versus non-familiar, males versus females, and individual identification versus emotional identification. Not only visual, but also auditory and even olfactory information may be involved in people recognition. Visual information involved in people recognition is proposed to include not only the perception of faces, but also the perception of whole body and gait, clothes, emotional expressions, and individual marks.